Methodological development of a wrestling shuttle test on the mat - Iwai, K.; Takahashi, R.; Yumoto, K.; Nakazato, K. (International scientific and professional conference on wrestling: "Applicable research in wrestling", 2017)
PURPOSE: Elite wrestlers have high aerobic and anaerobic capacities. They also acquire their sport-specific movements and techniques while wrestling. However, there is no wrestling shuttle test which requires wrestling-specific movements on the wrestling mats. Thus, this study methodologically developed a shuttle test for wrestlers to evaluate their aerobic and anaerobic capacities on the mat while using wrestling-specific movements. A convenient feature of this wrestling shuttle test is its easy administration in the practice room and without extraneous equipment. METHODS: Twenty-two Canadian wrestlers participated in this study (15 males and 7 females). We designed a wrestling shuttle test using a concept which includes 4 main standpoints; 1: wrestling-specific movements, 2: the international wrestling rules, 3: on the mat, 4: individuality. The wrestling-specific movements can have many directions depending on the wrestling styles with wrestlers and their opponents. Therefore, we decided that wrestlers should move in four directions by running forward, backward, and side-shuffling steps in both left and rightward directions. As shown in the Figure, the wrestling shuttle test was conducted on the wrestling mat. The length of each shuttle is 4 meters between the center circle and 3 designated points (., ., .) outside the mat circle (passivity zone). This shuttle test involves performing as many shuttle lengths as possible in 3 minutes (incomplete lengths were not recorded). A full cycle of 8 shuttle lengths (right side: lengths 1 to 4, left side: lengths 5 to 8) includes two lengths of each of the four movement directions, and is to be repeated as many times as possible by the wrestler. RESULTS: The normal distribution of scores were observed in this study (wrestling shuttle test: z = 1.042, p value = 0.228). We also confirmed similar results depended on sex (males: z = 0.622, p value = 0.833, females: z = 0.790, p value = 0.561). CONCLUSIONS: This study can suggest that the wrestling shuttle test we developed is an easy and convenient method to conduct measures of aerobic and anaerobic capacities on the wrestling mat.